PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KUE BAY TAT CHANAYA DI KOTA BENGKULU - Monica, Agnes; Bahrun, Khairul (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
The purpose of this study was to know the effect of product quality, price and promotion on the purchasing decision of Bay Tat Chanaya cake in Bengkulu City, and to know which factor is the most dominant affecting both partially and simultaneously. This study used a survey research method with quantitative data analysis. The population in this study are consumers who shop at Bay Tat Chanaya cake shop in Bengkulu City. The sampling used is the Accidental sampling method that was taken from the technique of determining the sample by chance, anyone who accidentallywere metby the researcher that can be used as a sample. The number of respondents in this study were 150 respondents. To be more efficient in obtaining data from respondents, researchers used questionnaire data. The data analysis technique used is the analysis technique that can be calculated, or data in the form of numbers and calculations by using statistical methods, then the data must be clarified in certain categories using the SPSS (Statistical Package For Social Scinences) program. Based on the results of multiple linear regression, the regression equation is Y = 0.672 + 0.330 (X1) + 0.267 (X2) + 0.209 (X3). The results of the research and the hypothesis show that the product quality shows the value of t_count > t Î± / 2 (4.109> 1.9762) and (sig Î± = 0,000 <0.050), the price shows the value of t_count > t Î± / 2 (3,280> 1.9762) and (sig Î± = 0.001 <0.050). Promotion shows the value of t count > t Î± / 2 (2,577> 1.9762) and (sig Î± = 0.011 <0.050). Simultaneously, the variables of Product Quality, Price and Promotion have a significant effect on purchasing decisions. Partially, the three variables of Product Quality, Price and Promotion have a significant effect on purchasing decisions. It is better if the shop owner can continue to maintain the quality of their products.Â Keywords: Product Quality, Price, Promotion, Purchase Decision.